ANALISIS KEBUTUHAN PERALATAN PADA PRAKTIK FINISHING BANGUNAN DI PROGRAM KEAHLIAN TEKNIK BANGUNAN SMK NEGERI 1 PADANG - Eko Purwono; Dr. Nurhasan Syah, M.Pd (Universitas Negeri Padang, 2019)
Abstract–. This research start from the observations by the author to the completeness of practice equipment at SMK Negeri 1 Padang. The purpose of this study was to determine needs of equipment and the level of availability forpractices Finishing Building in the Building Engineering Program at SMK Negeri 1 Padang.This type of research is a survey research using a quantitative approach and this research is descriptive. The method used in this study is the method of observation and interview (questionnaire). This analysis compares the equipment needed with what is available.This analysis compares the equipment available with the equipment needed. There are three classifications of equipment requirements such as: individual needs, group needs, classical needs. The results of this study indicate that in general the needs of equipment forpractices Finishing Buildingin the Building Engineering Program at SMK N 1 Padang are still many that are incomplete. The availability of equipment inpractices Finishing Buildingin the Building Engineering Expertise Program at SMK N 1 Padang is that there are still many individual and group needs that have not met the needs but in the classical needs are sufficient and required. Keywords: Needs Analysis, Needs Standard, Equipment